Character strengths at work: Predictive role of signature strengths and demanded strengths for work role performance and deviant behavior - Tahira Mubashar; Claudia Harzer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Character strengths are presumed to highlight those qualities that are best in people and reflect people's potential for achieving personal well-being and contributing to the workplace. The present study intended to corroborate the predictive role of character strengths and strengths use for self and supervisory ratings of job performance and deviant behavior. The sample consisted of employees (N = 178) who provided information about the study variables whereas their respective supervisors (N = 152) provided data for outcome variables (i.e., work role performance and deviant behaviors of the reporting employees). The findings showed that character strengths and strengths use are associated positively with self and supervisory-rated job performance and negatively with deviant behavior. Signature strengths use predicted self-rated work role performance while demanded strengths use predicted both self and supervisory-rated work role performance and deviance. The study suggests that the use of strengths at work improves one's work role performance and reduces the likelihood of deviant behaviors.
Keywords: 330; Values in Action; character strengths; signature strengths; demanded strengths; job performance; deviant behaviors